Kakeibo Method in Financial Management for Communities in Padanglampe Village - N. Nurfadila; Fyrdha Faradyba Hamzah; Moh. Zulkifli Murfat; Zalwa Dima Faradhiba; Dhia Aulia Shydqiah (Manunggal Halim Jaya, 2022)
This community service activity program aims to provide an understanding of efforts to manage finances to maintain family economic resilience, especially during the Covid-19 pandemic. The kakeibo method is a method of financial management that can be applied in financial management both within the household and for the general public. This will be the basis for managing good financial management even with this method can increase savings. This community service activity is in collaboration with the target village of the Indonesian Muslim University. The results obtained from this community service activity are increasing knowledge for the people of Padanglampe village regarding the kakeibo method in financial management. People experience difficulties in managing their finances because they cannot control their desires, which often misprioritizes spending. Financial management seems very simple, but in practice many people are not able to manage it properly.